2021
DOI: 10.1177/14791641211002470
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of tissue inhibitor of metalloproteinase-1 in patients with type 1 diabetes mellitus associate with early diabetic neuropathy and nephropathy

Abstract: Background: Tissue inhibitor of metalloproteinase-1 (TIMP-1) has been suggested as a marker for abnormal regulation of tissue remodelling in type 1 diabetes. Metalloproteinase-9 (MMP-9) has been associated with matrix turnover, and Neutrophil gelatinase associated lipocalin (NGAL) is a marker of tubular injury in diabetic nephropathy. The aim was to analyse these biomarkers to unmask early diabetic complications. Methods: Thirty-three type 1 diabetes patients, aged 20–35 years, and disease duration 20 ± 5.3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…Identifying risk factors (besides poor metabolic control) before complications from diabetes occur could also help doctors and nurses working with children and adolescents with type 1 diabetes to improve and personalise their treatment. Previous studies have suggested the association of circulating proteins as biomarkers of vascular disease in both adults and children with type 1 diabetes [9,10,30]. The current study observed increased sCD163 in patients with recent-onset type 1 diabetes with levels correlating to HbA1c.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Identifying risk factors (besides poor metabolic control) before complications from diabetes occur could also help doctors and nurses working with children and adolescents with type 1 diabetes to improve and personalise their treatment. Previous studies have suggested the association of circulating proteins as biomarkers of vascular disease in both adults and children with type 1 diabetes [9,10,30]. The current study observed increased sCD163 in patients with recent-onset type 1 diabetes with levels correlating to HbA1c.…”
Section: Discussionsupporting
confidence: 66%
“…Among other risk factors are high blood pressure and cholesterol levels [1]. Recently, studies have suggested soluble biomarkers which may identify the increased risk of developing diabetesrelated complications in adults [9] and young patients with type 1 diabetes [10]. These studies have found several markers correlating with risk for vascular complications in type 1 diabetes.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…( 6 ). Type 1 diabetes (SAID in the current study) is known to be associated with an increased risk of cardiovascular disease and microvascular complications ( 16 , 17 ), the main mechanism of which has not been fully clarified, but it may be partly related to the high levels of metalloproteinase-9 and metalloproteinase-1 tissue inhibitors in the plasma and tissues of patients with type 1 diabetes ( 18 ). The SIRD group has the highest incidence of DKD, which is consistent with the finding of previous reports ( 8 , 19 ) and may be related to the high smoking rate and lipid metabolism disorder in patients with SIRD.…”
Section: Discussionmentioning
confidence: 92%
“…TIMP1 belongs to the TIMP gene family, and the protein encoded by this gene family is a natural inhibitor of matrix metallopeptidase, which can regulate cell differentiation, migration, and cell death. It has been reported that plasma levels of TIMP1 are associated with early diabetic neuropathy and nephropathy in patients with type 1 diabetes ( 42 ). TPM1is a member of the highly conserved tropomyosin family, widely distributed actin-binding proteins that are involved in the contractile system of striated and smooth muscles and the cytoskeleton of non-muscle cells.…”
Section: Discussionmentioning
confidence: 99%